2011
DOI: 10.1186/1478-7954-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Use of verbal autopsy in a national health information system: Effects of the investigation of ill-defined causes of death on proportional mortality due to injury in small municipalities in Brazil

Abstract: BackgroundThe Mortality Information System (MIS) in Brazil records mortality data in hospitals and civil registries with the responsibility of compiling underlying cause of death. Despite continuous improvements in the MIS, some areas still maintain a high proportion of deaths assigned to ill-defined causes. Deaths coded to this category have most likely been considered as miscoded deaths from communicable and noncommunicable diseases. However, some local studies have provided evidence of underreporting of inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…The observed improvements seem to be very closely associated with investments in the public health care system and administrative procedures to collect vital statistics 1,32,33 . Thus, the quality of mortality data for adults seems to have expressively improved through the years and across many regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The observed improvements seem to be very closely associated with investments in the public health care system and administrative procedures to collect vital statistics 1,32,33 . Thus, the quality of mortality data for adults seems to have expressively improved through the years and across many regions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a higher proportion of ill-defined causes of death are found among the elderly and small children, are more concentrated in less-developed regions of the country and that most of them happened outside a health facility 1,25,31,33 . We should expect that the number of ill-defined causes of death would decrease as improvements in diseasediagnosis develop over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 As áreas com sistemas de informações que apresentem baixos valores nos indicadores de qualidade merecem, portanto, ações específicas que levem em consideração suas peculiaridades, para que o avanço na qualidade da informação seja evidenciado em todas as regiões do país e dos estados. 31 Assim como na maior parte mundo, as taxas de incidência e mortalidade do CCU têm mostrado um declínio nos dados nacionais do Brasil, 3,4,10,16,20,32 onde, nos últimos anos, as doenças crônicas não transmissí-veis -DCNT -têm sido foco de políticas de prevenção, promoção da saúde, e de trabalhos intersetoriais integrados com a assistência médica. 33,34 Desde então, o país vem ampliando a cobertura populacional de oferta de exames citopatológicos e o número de laboratórios com capacidade para realizá-los.…”
Section: Discussionunclassified